Consumer Attitudes towards Femvertising in Russia and Türkiye: A Netnographic Study - Iana Aleksandrova; Tuba Çevik Ergin (Sakarya İletişim)
This research paper examines consumer attitudes towards femvertising within the context of Nike's campaigns in Russia and Turkey. Through a netnographic analysis of YouTube comments, the research reveals how gender, cultural and political context influence responses to women’s empowerment messages in advertising. While women in both countries largely responded positively to femvertising, perceiving it as empowering and motivational, men’s reactions were more polarized. Russian men displayed substantial resistance, with many viewing the advertisement’s feminist undertones negatively and interpreting it as an imposition of Western feminist ideas that undermine traditional values. This opposition aligns with Russian political discourse, which in recent years has shifted towards the preservation and reinforcement of traditional spiritual and moral values. In contrast, Turkish men were relatively more receptive to femvertising messages, though they still expressed some caution. Turkey’s more varied discourse on gender, which balances secular ideas and traditional Islamic values, contributed to a less polarized reaction to femvertising. The study underscores the importance of authenticity in femvertising, noting the potential for backlash and skepticism towards commercialized feminism, particularly among male audiences. It also highlights the importance of diversity, recommending the inclusion of men, alongside women of varied religions, body types, and appearances, to foster inclusivity and prevent discrimination. These findings enrich the literature on gender-focused advertising, emphasizing the importance of cultural sensitivity and adherence to authentic femvertising principles when employing femvertising strategies across diverse cultural landscapes.